Study of canthal index in Nepalese undergraduate medical students of BPKIHS, Nepal: gender and ethnic differences - Shah, Sandip; Koirala, Sarun (Journal of Kathmandu Medical College, 2014)
Background: Craniofacial anthropometry is a technique used in both physical and clinical anthropology comprising precise and systematic measurements of the human skull. It also includes measurement of the medial and lateral canthal distances. People of different genetic background subjected to significantly different environmental influences have different craniofacial morphology. Objectives: To find out effect of gender and ethnicity on Canthal anthropometry. Methods: This descriptive cross-sectional study was carried out to determine and compare canthal anthropometry among 299 undergraduate students (Male=161, Female=138) of different ethnic groups (Indo-Nepalese, indigenous and Tibeto-Nepalese) of age group 19-21 years at BPKIHS. Medial and lateral canthal distances were measured by using straight vernier caliper and canthal index (medial canthal distances / lateral canthal distance × 100) for all three ethnic groups in both sexes were compared. Results: The study has shown that the female students had higher canthal index than male students (27.65±12.35 vs 23.96±5.76). When compared on the basis of ethnicity, Indo-Nepalese had highest value of canthal index followed by Indigenous and Tibeto-Nepalese. Conclusion: In conclusion, genetics and environmental factors are responsible for the variation in canthal indices and other craniofacial indices between and within populations. Therefore, its standard values are largely applicable for clinical assessment of patients with syndrome affecting canthal anatomy. DOI: http://dx.doi.org/10.3126/jkmc.v3i2.11231 Journal of Kathmandu Medical College Vol. 3, No. 2, Issue 8, Apr.-Jun., 2014 Page: 78-81